Randomised controlled trial of the effect of long-term selenium supplementation on plasma cholesterol in an elderly Danish population. Issue 11 (30th September 2015) - Cold, Frederik; Winther, Kristian H.; Pastor-Barriuso, Roberto; Rayman, Margaret P.; Guallar, Eliseo; Nybo, Mads; Griffin, Bruce A.; Stranges, Saverio; Cold, Søren
Abstract: Although cross-sectional studies have shown a positive association between Se and cholesterol concentrations, a recent randomised controlled trial in 501 elderly UK individuals of relatively low-Se status found that Se supplementation for 6 months lowered total plasma cholesterol. The Danish PRECISE (PREvention of Cancer by Intervention with Selenium) pilot study (ClinicalTrials.gov ID: NCT01819649) was a 5-year randomised, double-blinded, placebo-controlled trial with four groups (allocation ratio 1:1:1:1). Men and women aged 60–74 years ( n 491) were randomised to 100 ( n 124), 200 ( n 122) or 300 ( n 119) μg Se-enriched yeast or matching placebo-yeast tablets ( n 126) daily for 5 years. A total of 468 participants continued the study for 6 months and 361 participants, equally distributed across treatment groups, continued for 5 years. Plasma samples were analysed for total and HDL-cholesterol and for total Se concentrations at baseline, 6 months and 5 years. The effect of different doses of Se supplementation on plasma lipid and Se concentrations was estimated by using linear mixed models. Plasma Se concentration increased significantly and dose-dependently in the intervention groups after 6 months and 5 years. Total cholesterol decreased significantly both in the intervention groups and in the placebo group after 6 months and 5 years, with small and nonsignificant differences in changes in plasma concentration of total cholesterol, HDL-cholesterol, non-HDL-cholesterol and total:HDL-cholesterol ratio between intervention and placebo groups. The effect of long-term supplementation with Se on plasma cholesterol concentrations or its sub-fractions did not differ significantly from placebo in this elderly population.